The Impact of Oil Prices Fluctuations on Industrial Production in G20 Countries - Rahmouni, Oubeid; Al Kahtani, Dalal (International Journal of Energy Economics and Policy, 2025)
This paper analyzes the impact of oil prices fluctuations on industrial production in G20 countries, since it includes the largest economies in the world, and it also, consists of major oil exporters and importers countries. Therefore, an industrial production function is estimated with an Autoregressive Distributed Lags model (ARDL) and explained with a set of economic variables such as foreign direct investment, trade openness, the economic freedom index, and gross fixed capital formation, in addition to real oil prices, for the period (1979-2020). This study uses the Pooled Mean Group Dynamic Panel Data estimator (PMG) because it considers the hypothesis of long-term homogeneity between countries, given their interconnection in terms of the size of their economies and the volume of trade exchange. On the other hand, this method assumes heterogeneity in the short term because countries differ within the oil position and adopt policies in response to oil price changes. The main result is that thanks to the energy source diversification policies adopted since the 1970th oil shocks, these countries have successfully minimized the impact of these fluctuations. Thus, in the short term, oil prices do not affect the dependent variable; this impact becomes negative but very limited in the long term.